2010
DOI: 10.1016/j.vaccine.2009.11.030
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, dose-finding Phase II study to evaluate immunogenicity and safety of the third generation smallpox vaccine candidate IMVAMUNE®

Abstract: IMVAMUNE® is a Modified Vaccinia Ankara-based virus that is being developed as a safer 3 rd generation smallpox vaccine. In order to determine the optimal dose for further development, a double-blind, randomized Phase II trial was performed testing three different doses of IMVAMUNE® in 164 healthy volunteers. All three IMVAMUNE® doses displayed a favourable safety profile, with local reactions as the most frequent observation. The 1×10 8 TCID 50 IMVAMUNE® dose induced a total antibody response in 94% of the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
98
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 35 publications
(48 reference statements)
7
98
0
5
Order By: Relevance
“…Maximum mean peak fold changes in IFN-␥ (8,028), IL-1ra (4,854), and IL-6 (3,207) were recorded on a variety of days (8). In this study, the mean peak changes in the biomarkers IFN-␥ (1,322 pg ml Ϫ1 ), IL-1ra (3,335 pg ml Ϫ1 ), and IL-6 (570 pg ml Ϫ1 ) occurred on day 8 postchallenge.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Maximum mean peak fold changes in IFN-␥ (8,028), IL-1ra (4,854), and IL-6 (3,207) were recorded on a variety of days (8). In this study, the mean peak changes in the biomarkers IFN-␥ (1,322 pg ml Ϫ1 ), IL-1ra (3,335 pg ml Ϫ1 ), and IL-6 (570 pg ml Ϫ1 ) occurred on day 8 postchallenge.…”
Section: Discussionmentioning
confidence: 48%
“…Recently, the majority of the human population has not been vaccinated; consequently, a proportion of the population lacks protective immunity (3). Concerns over the use of variola virus or monkeypox virus (a closely related orthopoxvirus) as a biological weapon remain high, as a deliberate release would have catastrophic consequences on global health (4).…”
mentioning
confidence: 99%
“…No significant adverse events were reported after the administration of MVA to more than 120,000 primary vaccinees in Germany (27,45). Recent clinical studies using a third-generation vaccine, MVA-BN, as a stand-alone smallpox vaccine confirmed its excellent safety profile (56,57) and underscored its potential as a safe vaccine vector against human infections with various pathogens as well as against cancer.…”
mentioning
confidence: 99%
“…MVA-BN was further developed from MVA of passage number 572 by limiting dilution and passaging and proved to be safe even in severely immunocompromised hosts (29,46). Recent clinical studies using MVA-BN as a third-generation standalone smallpox vaccine confirmed its excellent safety profile in humans (50,51) and underscored its potential as a safe vaccine and gene therapy vector.…”
mentioning
confidence: 99%